2021
DOI: 10.1002/jmri.27829
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Non‐Contrast‐Enhanced Dixon Water‐Fat Separation Compressed SENSE Whole‐Heart Coronary MR Angiography at 3.0 T With and Without Nitroglycerin

Abstract: Background3.0 T non‐contrast‐enhanced nitroglycerin (NTG)‐assisted whole‐heart coronary magnetic resonance angiography (MRA) employing Dixon water‐fat separation and compressed SENSE (CS‐SENSE) acceleration is a promising method for diagnosing coronary artery disease (CAD).PurposeTo evaluate the diagnostic performance of this technique for detecting clinically‐relevant (≥50% diameter reducing) CAD and to evaluate the difference in NTG‐induced coronary vasodilation between patients with and without clinically‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A previous study has found that the Dixon water-fat method provides improved non-contrast coronary MRA image quality at 3T compared to the conventional spectral inversion recovery (SPIR) technique [32]. In a study from 2022, Lu et al have demonstrated the feasibility of 3T non-contrast water-fat separated coronary MRA for detect clinically significant coronary stenosis [34]. There are two relatively quiescent periods in the cardiac cycle for acquiring images, mid-diastole and end-systole, lasting for an average of 187 ms and 118 ms [6] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has found that the Dixon water-fat method provides improved non-contrast coronary MRA image quality at 3T compared to the conventional spectral inversion recovery (SPIR) technique [32]. In a study from 2022, Lu et al have demonstrated the feasibility of 3T non-contrast water-fat separated coronary MRA for detect clinically significant coronary stenosis [34]. There are two relatively quiescent periods in the cardiac cycle for acquiring images, mid-diastole and end-systole, lasting for an average of 187 ms and 118 ms [6] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A free-breathing, non-contrast, Dixon water-fat separation 3D whole-heart MRI sequence was applied ( 21 ), with the following settings: time to echo (TE), 1.54 ms; repetition time (TR), 3.5 ms; flip angle, 10 ° ; compressed sensing (CS) factor, 2.5; k-space Cartesian; matrix, 256 × 184 × 250 mm; mDIXON, ECG-gated; the trigger delay, 240–300 ms of the temporal window. This acquisition window was determined by a four-chamber view of the left ventricle with reduced motion and a turbo field echo (TFE) shot duration of 80–130 ms, depending on the heart rate.…”
Section: Methodsmentioning
confidence: 99%
“…In Lu et al, 8 the authors used a 3 T noncontrast‐enhanced Dixon water‐fat separation coronary MR angiography with CS reconstruction techniques to detect significant CAD and evaluate the difference in the effect of sublingual nitroglycerin on coronary vasodilation between the significant CAD and the nonsignificant CAD groups. They also demonstrated that sublingual nitroglycerin enhanced the visibility of the coronary arteries, thereby improving the diagnostic performance of the proposed method.…”
mentioning
confidence: 99%